Advance care planning imperative: High-quality patient-centred goals of care. Issue 4 (27th April 2022) - Case, Amy Allen; Epstein, Andrew S; Gustin, Jillian L.
Abstract : Advance care planning (ACP) discussions aim to ensure goal-concordant care for patients with serious illness, throughout treatment and especially at the end of life. But recent literature has forced the field of palliative care to wrestle with the definition and impact of ACP. Are ACP discussions worthwhile? Is there a difference between ACP discussions early in a patient's illness versus discussions occurring later when a concrete medical care decision must be made? Here, we identify elements needed to answer these questions and describe how a multisite initiative will elucidate the value of discussing and documenting what matters most to patients.